Institutions, institutional change, and economic performance - North, Douglass C. (Douglass Cecil), 1920- (Cambridge ; New York : Cambridge University Press, 1990)
Institutions. Institutional change. Economic performance.
Keywords: Economic development; Institutional economics; Organizational change; Economic development; Organizational change; Organizational innovation; Institutional economics